A diagnostic flow chart for POLG-related diseases based on signs sensitivity and specificity. Issue 6 (11th August 2014) - Tchikviladzé, Maya; Gilleron, Mylène; Maisonobe, Thierry; Galanaud, Damien; Laforêt, Pascal; Durr, Alexandra; Eymard, Bruno; Mochel, Fanny; Ogier, Hélène; Béhin, Anthony; Stojkovic, Tanya; Degos, Bertrand; et al.
Abstract : Objective: Diseases due to mutations of POLG gene, encoding the mitochondrial DNA polymerase, are reputed to have very diverse clinical presentations and have been proposed to cause up to 25% adult mitochondrial diseases. Our objective was the evaluation of the specificity and sensitivity of the signs encountered with POLG mutations. Design: Forty-four patients out of 154 with sequenced POLG gene had mutations affecting either one ( POLG +/− group) or two POLG alleles ( POLG +/+ group). Phenotyping included clinical signs, electroneuromyography and brain imaging while mitochondrial investigations encompassed muscle histochemistry, respiratory chain assays and search for multiple mitochondrial deletions. The specificity and sensitivity of the signs associated with POLG mutations were analysed by comparison between POLG +/+ and patients without POLG mutation. Results: High sensitivity but low specificity was observed with single signs such as axonal sensory neuropathy, cerebellar syndrome, movement disorders and weakness involving ocular, pharyngeal, axial and/or limb muscles. Specificity was increased with combination of previous signs plus psychiatric symptoms, cognitive impairment and epilepsy. High specificity and sensitivity was only obtained with sensory neuronopathy associated with one of the following signs: weakness of ocular, pharyngeal, axial and/or limb muscles. Mitochondrial investigations did not suffice for diagnosis. The widespread neuromuscular signs were often present since disease onset and were the rule above 50 years of age leading to a very low probability of POLG mutations in patients with less than three signs and absent sensory neuropathy. Conclusions: Phenotypes associated with POLG mutations follow a reproducible pattern, which allows establishing a diagnostic flow chart.